Strategi Meningkatkan Skill Communication Santri Melalui Kegiatan Muhadharah di Ma’had Ulul Albab MAN 2 Lamongan - Muhammad Adiib (Advance Journal of Education and Religion (AJER) published by Fakultas Agama Islam Universitas Islam Darul 'Ulum Lamongan, 2026)
This research is motivated by the importance of communication skills in shaping the personality of students (santri) to face 21st-century challenges. At Ma’had Ulul Albab MAN 2 Lamongan, muhadharah (public speaking activities) serves as the primary strategy for training students to speak in public. However, several obstacles persist, such as low self-confidence, over-reliance on scripts, and difficulties in interaction. This study aims to describe the implementation, strategies, and benefits of muhadharah activities in improving students' communication skills. The research method employed is descriptive qualitative with a field study approach. Data collection techniques include participatory observation, semi-structured interviews, and documentation. The research informants consist of the head of the ma’had, teachers (ustadzah), and students active in muhadharah activities. The results indicate that muhadharah activities are implemented structurally using a rotation system and evaluations from supervisors. The strategies used include continuous training, personal mentoring, motivation, and variations in delivery methods, such as memorizing and understanding the material. Students demonstrated improvements in courage, speaking fluency, and the ability to convey ideas systematically. In conclusion, muhadharah activities are effective as a strategy to enhance students' communication skills. This study suggests that the ma’had should continuously evaluate and develop muhadharah methods to be more varied and adaptive to modern needs, while providing intensive assistance for students who still face communication barriers.